Provincial Real Economic Growth in Indonesia: Investigating Key Factors Through Spatial Analysis - Muzzakar, Kahar; Syahnur, Sofyan; Abrar, Muhammad (Ekonomikalia Journal of Economics, 2023)
This study addresses the need to understand provincial real economic growth, as measured by gross regional domestic product (GRDP), by conducting a spatial analysis. The study focuses on the influential factors of physical investment, working labor force, social infrastructure relative to the head-count index of poverty, and human development index (HDI). Data from 34 provinces spanning eight years (2015-2022) were examined using geographically weighted panel regression with a fixed effect of provincial units and adaptive bisquare kernel function as spatial weights. The study identifies distinct spatial patterns in the variable impact on provincial real economic growth, forming groups based on influential factors. Physical investment and HDI significantly drive growth in most provinces. The working labor force strongly impacts Papua Island’s growth. Intriguingly, social infrastructure relative to the head-count index of poverty link to economic growth emerges in the central and eastern regions of Indonesia (Kalimantan, Sulawesi, Maluku, and Papua), highlighting its role in poverty reduction and inclusive growth. The findings highlight the importance of region-specific policies to optimize the potential of these variables and promote balanced economic growth across the province.